Muscle Invasive Bladder Cancer With Chronic Kidney Disease: A Case Report - Kusdianto, Hendro; Ramadhani, Muflikhah; Triwibowo, Suryo Prasetyo; Guntarno, Novalia Chumaladewi (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Bladder cancer ranks as the second most prevalent urinary tract cancer globally, following prostate cancer, accompanied by a significant mortality rate, and cause several complications, for example weight loss, urinary tract infections, metastases to other organs, and can cause chronic kidney failure due to obstruction of urine flow Objective: This case presented the challenging progression of muscle invasive bladder cancer with chronic kidney disease complications and refuse therapies as a clinical lesson for case management. Case Presentation: This case reports the clinical course of a 78 year old man who presented to our hospital's urology clinic presenting with symptoms of hematuria, along with urinary dripping and discomfort. Result: The patient was diagnosed with muscle invasive bladder carcinoma, with a complication of chronic kidney disease, and refused therapies. Conclusion: Controlling bladder cancer that has invaded to the muscular layer and chronic kidney disease was difficult and give poor prognosis linked to their age, type of bladder cancer, and refusal to undergo therapies.